Medication reconciliation on admission in paediatric chronic patients: A multicentre study - Margarita Cuervas-Mons Vendrell; Dolores Pilar Iturgoyen Fuentes; Joëlle Arrojo Suárez; Inés Jimenez Lozano; Cecilia Martínez Fernandez-Llamazares; Angela Tristancho-Perez; Lucia Yunquera Romero; Cristina Martínez Roca; Cristina Otero Villalustre; Ana García Robles; Beatriz Garrido Corro; Belén Rodríguez Marrodán (Anales de Pediatría (English Edition), 2023)
Introduction: Medication reconciliation (MC) is one of the main strategies to reduce medication errors in care transitions. In Spain, several guidelines have been published with recommendations for the implementation and development of MC aimed at the adult population, although paediatric patients are not included. In 2018, a study was carried out that led to the subsequent publication of a document with criteria for selecting paediatric patients in whom CM should be prioritised. Objectives: To describe the characteristics of paediatric patients most likely to suffer from errors of reconciliation (EC), to confirm whether the results of a previous study can be extrapolated. Methodology: Prospective, multicentre study of paediatric inpatients. We analysed the CE detected during the performance of the CM on admission. The best possible pharmacotherapeutic history of the patient was obtained using different sources of information and confirmed by an interview with the patient/caregiver. Results: 1043 discrepancies were detected, 544 were identified as CD, affecting 317 patients (43%). Omission of a drug was the most common error (51%). The majority of CD were associated with drugs in groups A (31%), N (23%) and R (11%) of the ATC classification. Polymedication and onco-haematological based disease were the risk factors associated with the presence of CD with statistical significance. Conclusions: The findings of this study allow prioritisation of CM in a specific group of paediatric patients, favouring the efficiency of the process. Onco-haematological patients and polymedication are confirmed as the main risk factors for the appearance of CD in the paediatric population. Resumen: Introducción: La conciliación de la medicación (CM) es una de las principales estrategias para disminuir los errores de medicación en las transiciones asistenciales. En España existen publicadas diferentes guías con recomendaciones para la implantación y desarrollo de la CM orientadas a población adulta, sin estar los pacientes pediátricos incluidos. En el año 2018 se llevó a cabo un estudio que permitió la posterior publicación de un documento con criterios de selección de pacientes pediátricos en los que priorizar la CM. Objetivos: Describir las características de los pacientes pediátricos con mayor probabilidad de sufrir errores de conciliación (EC), para confirmar si los resultados de un estudio previo son extrapolables. Metodología: Estudio prospectivo y multicéntrico con pacientes pediátricos ingresados. Se analizaron los EC detectados durante la realización de la CM al ingreso. La mejor historia farmacoterapéutica posible del paciente fue obtenida utilizando diferentes fuentes de información y confirmándose con una entrevista con el paciente/cuidador. Resultados: Se detectaron 1.043 discrepancias, determinándose como EC 544, afectando a 317 pacientes (43%). La omisión de algún medicamento fue el error más común (51%). La mayoría de los EC se asociaron con los medicamentos de los grupos A (31%), N (23%) y R (11%) de la clasificación ATC. La polimedicación y la enfermedad de base onco-hematológica fueron los factores de riesgo asociados a la presencia de EC con significación estadística. Conclusiones: Los hallazgos de este estudio permiten priorizar la CM en un grupo concreto de pacientes pediátricos, favoreciendo la eficiencia del proceso. Los pacientes onco-hematológicos y la polimedicación se confirman como los principales factores de riesgo para la aparición de EC en población pediátrica.